Using Community Radio to Create Awareness of Security Tips Related to Kidnapping in Nigeria - Sunday Samuel Ameh (Mdooter Journal of Communication and Digital Technologies)
Objective: This study sought to assess the use of community radio to raise awareness of security tips related to kidnapping in Nigeria. The study's objectives include identifying the degree to which community radio can be effective in raising awareness and ascertaining how community radio can be used to raise awareness in the state.